Penerapan Tutor Sebaya Untuk Meningkatkan Hasil Belajar Matematika Siswa Pada Materi Komposisi Fungsi - Ira Yulita; Moh. Syadidul Itqan; Dwi Rahayu Ningsih (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to improve students' mathematics learning outcomes in the function composition material through the implementation of peer tutoring strategies in class XI MA Islamiyah Syafi'iyah. This study uses the Kurt Lewin Classroom Action Research (CAR) model which is implemented in two cycles, with each cycle consisting of planning, action implementation, observation, and reflection. The research subjects were 29 students, and data were collected through observation of learning activities and learning outcome tests at the end of each cycle. Data analysis was carried out using the N-Gain calculation to determine the improvement in learning outcomes between cycles. The results showed a significant improvement in learning outcomes after the implementation of the peer tutoring strategy. The average N-Gain value in cycle I was 0.53 (52.84%) with a moderate category, increasing in cycle II to 0.79 (79.45%) with a high category. This increase indicates that the implementation of the peer tutoring strategy is effective in improving conceptual understanding, student activeness, and mathematics learning outcomes in the function composition material. Thus, the peer tutoring strategy can be used as an effective and interactive learning alternative to help students understand mathematics material more deeply.